The effects of initiator content on sago (metroxylon rottb.) starch-G-PAN hydrogel - Omar, Nurizan; Ahmad, Zuraida (Trans Tech Publications, Switzerland, 2013)
This paper explores the effects of ammonium persulphate (S-PANHs) content (1wt % - 5 wt %) to the properties of sago starch-graft-polyacrylonitrile hydrogels (S-PANH). S-PANHs were prepared via graft copolymerization of polyacrylonitrile (PAN) onto sago starch in the presence of ammonium persulphate (APS) as initiator and N, N-methylenebisacrylamide (MBA) as crosslinker. The percentage of water absorbency is observed to increase with increasing initiator content from 1wt% until reaching optimum point of 3 wt% APS. 48.78 % water absorbency was recorded at 3 wt% APS sample. The morphology of the hydrogels from the micrographs captured via scanning electron microscope (SEM) revealed the existence of pores and matching with the results of percentage water absorbency. Fourier transform infrared (FTIR) spectroscopy proved that the grafting process had occurred in S-PANH.